Pharmaceutical Pricing and Reimbursement Information (PPRI): a European Union project (Italian Journal of Public Health, 2006)
Background: In the European Member States, the systems for pharmaceutical pricing and reimbursement differ significantly. Amongst the administration and policy-makers at both national and European levels there is a lot of interest in the different pharmaceutical systems of the Member States as a means of learning from their experiences in pricing and reimbursement.Objectives: The general objective of the PPRI–Project – started in April 2005 - is to develop a network of authorities and institutions in order to improve information and knowledge on the pharmaceutical systems in the enlarged European Union. This network should facilitate a regular exchange of information and allow a process of learning from each other.Project description: The PPRI project team consists of the main partner (ÖBIG), an associated partner (WHOEURO) and a network of partners and observers which represent national stakeholders from almost all EU Member States and a number of international stakeholders. The information on pharmaceutical pricing and reimbursement will be collected and summarised in country reports (“Pharma Profiles”) which follow a homogenous structure. The individual country’s information will be analysed and compared on the basis of a set of indicators (benchmarks).Deliverables:The main deliverables of the project are: • Pharma Profiles, • a benchmarking report, in which pharmaceutical pricing and reimbursement in the Member States is compared,• a website containing information on the project and on pricing and reimbursement in the Member States, and • a conference at the end of the project during which the study results will be disseminated.
Keywords: Pharmaceuticals; pricing; reimbursement; Europe; PPRI